Election night Bruce Bronzan Victory for District 3 Supervisor - Watkins, Howard K. (1976)
Molly Miles opening box of roses surrounded by campaign volunteers Max Cheeseman, Bill Carlson, Doug Jones, Raul Martinez, ?? Bev Anderson, Steve Morgan, Chloe French, Nyla Hallum